IMPLEMENTASI TEKNOLOGI TEPAT GUNA ALAT PRESS HIDROLIK DI USAHA PENGEPUL BESI TUA DAN BARANG BEKAS TERANG JAYA - Mazwan; Sukadi; Satrio Darma Utama (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to improve the efficiency and effectiveness of solid waste management at Terang Jaya Scrap Metal and Recyclable Goods Enterprise through the implementation of an innovative hydraulic press machine. Previously, the process of packing aluminum cans, plastic bottles, and cardboard was carried out manually, requiring considerable time, large storage space, and intensive labor. The program was conducted through several stages, including needs assessment, design and fabrication of the press machine, handover to the partner, and training on operation and maintenance. The results showed that the use of the press machine reduced waste volume by up to 70% and shortened the packing time from an average of 25 minutes to 8–10 minutes per batch. In addition to improving operational efficiency, the partner demonstrated increased skills in machine operation and greater awareness of the importance of efficient and environmentally friendly waste management. This program has had a positive impact on productivity and business sustainability, serving as a model for the application of appropriate technology that can be replicated by similar small-scale recycling enterprises to support more effective and sustainable waste management practices.